THE TEACHING LISTENING PROCES AT THE FIRST YEAR STUDENTS OF ENGLISH DEPARTMENT OF UIN AR-RANIRY BANDA ACEH - Dara Yusnida (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2020)
The researcher tried to investigate the process of teaching learning listening at the first-year students of English Department of UIN Ar-Raniry in terms of (a) classroom activities, (b) the using of media, (c) strategy used, and (d) feedback. This study employed a descriptive qualitative method. Two English listening lecturers had been chosen as the subjects of this study. Observation and interview were used to collect the data. Then the researcher analyzed and interpreted through qualitative procedures by using data reduction, data presentation, verification and conclusion drawing. The finding displayed that the two lecturers had different styles of teaching activities in the classroom and teaching media have been selected by them. The teaching strategy used by the English lecturers were various and agreed with the theories of the teaching of listening. Both of the lecturers provided appropriate feedback and corrections.